Congruent routing protocols in diverse tree topology ZigBee built home area networks. (2020) - Rajesh kanna, B.; Anitha, M.
Abstract: At the residential level, the important services of smart grid namely Advanced metering infrastructure and Demand response are accomplished by the smart energy devices such as smart electrical appliances and smart meters to support dynamic price, bill, control from the utility and export of surplus power. To enhance the quality and reliability of smart grid services and power dispatch, ZigBee built smart energy home area networks are deployed as the last hop of smart grid networks to collect real-time home data. However, routing is the major issue in determining the efficacy of such networks. Moreover, ZigBee employs a tree addressing scheme that helps in assigning unique address to each node in network. This paper evokes congruent routing protocols such as ZigBee shortcut tree routing (ZSTR), ZigBee opportunistic STR, ZigBee directional OSTR, Energy Potent STR for tree topology and a Linear path cluster tree routing for long thin tree topology. Exclusively, this paper proposes a new routing named Energy potent ZigBee directional opportunistic short-cut routing and show its performances in routing, congestion management, bandwidth utilization enhancement, network lifetime expansion and power consumption reduction comparatively with other five diverse routings.